2010
DOI: 10.1063/1.3427406
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial graphene on cubic SiC(111)/Si(111) substrate

Abstract: Epitaxial graphene films grown on silicon carbide ͑SiC͒ substrate by solid state graphitization is of great interest for electronic and optoelectronic applications. In this paper, we explore the properties of epitaxial graphene films on 3C-SiC͑111͒/Si͑111͒ substrate. X-ray photoelectron spectroscopy and scanning tunneling microscopy were extensively used to characterize the quality of the few-layer graphene ͑FLG͒ surface. The Raman spectroscopy studies were useful in confirming the graphitic composition and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 21 publications
6
67
0
Order By: Relevance
“…This is consistent with 3C -SiC(111) which is the SiC polytype expected to grow on Si(111) at these temperatures [13]. The black arrows point out diffraction spots that, although not well-resolved, could correspond to the √ 3 × √ 3 reconstruction which has been observed for this surface [14,15]. The graphitic nature of the carbon film on samples #2, #3 and #4 and the carbide nature of the film on sample #1 are further confirmed by XPS data on C 1s core level shown in Fig.…”
supporting
confidence: 82%
“…This is consistent with 3C -SiC(111) which is the SiC polytype expected to grow on Si(111) at these temperatures [13]. The black arrows point out diffraction spots that, although not well-resolved, could correspond to the √ 3 × √ 3 reconstruction which has been observed for this surface [14,15]. The graphitic nature of the carbon film on samples #2, #3 and #4 and the carbide nature of the film on sample #1 are further confirmed by XPS data on C 1s core level shown in Fig.…”
supporting
confidence: 82%
“…8 The structural and electronic properties of such graphene were comparable to those of graphene on SiC(0001). 9,10 The first carbon layer that grows on top of SiC(111) is known as zero-layer graphene (ZLG).…”
mentioning
confidence: 84%
“…Most of the works employing either 3C-SiC substrates or 3C-SiC templates on Si(111) for the growth of graphene focused on Si-face material. [8][9][10][11][12] Only two works on C-face graphene grown on 3C-SiC(111) by low-10 and high-temperature 11 sublimation in a ultra-high vacuum and an argon atmosphere, respectively, have been published. Both studies reported that C-face graphene grows without the formation of a buffer layer in similarity to the situation for FLG on 4H-and 6H-SiC.…”
mentioning
confidence: 99%
“…We also note the absence of the D peak in the Raman spectra of our sample, which is in sharp contrast to all published results for Si-and C-face graphene on 3C-SiC(111), where a very strong D peak is commonly observed. [8][9][10] The D mode is Raman inactive and requires defects to be activated and its intensity with respect to that of the G peak is related to the defect density. From the absence of the D peak in the Raman spectra of our sample, we estimated a lower limit of the average distance between defects in the C-face graphene on 3C-SiC (111) to be !100 nm.…”
mentioning
confidence: 99%